Using the theoretical domains framework to guide the development of a self-management program for individuals with spinal cord injury: Results from a national stakeholder advisory group. (2nd November 2017) - Munce, Sarah E.P.; Allin, Sonya; Wolfe, Dalton L.; Anzai, Karen; Linassi, Gary; Noonan, Vanessa K.; Jaglal, Susan B.
Abstract : Objective: To determine the implementation considerations for a targeted self-management program for individuals with spinal cord injury (SCI) from the perspective of a national stakeholder advisory group using the Theoretical Domains Framework (TDF) as a guide. Design: Qualitative descriptive approach. Setting: Two focus groups held at the 6 th National Spinal Cord Injury Conference (October 2–4 th, 2014) in Toronto, Ontario, Canada. Participants: A total of 25 stakeholders from across Canada participated in focus groups or "brainstorming sessions". The stakeholders included 5 clinicians, 14 researchers, 3 policy makers, and 3 individuals with SCI. Interventions: Not applicable. Outcome Measures: Not applicable. Results: All 14 theoretical domains were identified in the brainstorming sessions. No new themes or domains were identified. The need to consider the theoretical domains of Knowledge, Skills, Reinforcement, Intentions, Goals (e.g. the readiness of the individual with SCI), Environmental Context and Resources (e.g. considerations for governance and ownership of the program and a business model for sustainability), as well as Social Influences (e.g. issues of privacy and security in the context of on-line delivery) was identified. Conclusions: The current study provides complementary results to our previous series of studies on the implementation considerations for the development of a targeted self-management program for individuals with SCI by emphasizing the health care professional/health policy perspective. It is anticipated that such a program could not only reduce secondary complications and subsequent inappropriate health care use but it may also improve the quality of life for individuals with SCI and their caregivers.